Macrofungi from Siddababa Sacred Grove: West, Nepal - Aryal, Hari P; Poudel, Rajenda; Budathoki, U (Journal of Agriculture and Environment, 2014)
During the survey of wild edible mushrooms in between tropical and temperate belt of Nepal in rainy season 2010 -2012, many macro fungal species were collected and identified. The paper highlights on new record of Volvorella taylorii (Berk and Broome) Sing. The species was reported and re-described for the first time from Nepal. Along with, taxonomic description of the two species of Volvorella found in the same studied area, have also been provided. Phytogeographycally, the sample collected area lies within a narrow limit of 9.75 hectare at the altitude between 335 and 400 masl in tropical deciduous riverine forest. The dried specimens are housed in the Tribhuvan University Central Herbarium (TUCH), Kirtipur Kathmandu, Nepal.